Comparative analysis of co-culture and monoculture models in simulating diabetic neurovascular dysfunction: insights into diabetic retinopathy - Wang, Qiyun; Qiao, Zhixin; Kang, Wenting; Zhu, Ling; Zhang, Xinyuan (Frontiers in Endocrinology, 2023)
Background: Interaction between retinal vascular endothelial cells and neurons plays a critical role in the pathogenesis of diabetic retinopathy (DR). This study aims to compare an in vitro model over a monoculture model to simulate the neurovascular coupling under the hyperglycemic microenvironment of diabetes.Methods: Rat retinal vascular endothelial cells (RRMECs) and ganglion cells (RGCs) were seeded mono-or co-cultured in a normal (NG, 5.5 mM) and high (HG, 75 mM) glucose concentrations culture medium. Cell viability was detected by the cell counting kit-8 (CCK-8) assay. The ability of migration and lumen formation of RRMECs were determined by scratch wound, transwell migration, and lumen formation assays. The apoptosis index of cells was calculated and detected by propidium iodide (PI)/Hoechst staining. Quantitative and morphological analysis of RGCs was performed through the labeling of RGCs by brain-specific homeobox/POU domain protein 3A (BRN3A) and anti-beta-III tubulin (TUJ1). The gene and protein expression levels of occludin (OCLN) and zonula occludens-1 (ZO-1) were evaluated by quantitative real-time polymerase chain reaction and enzymelinked immunosorbent assay.The viability, migration, and lumen formation abilities of RRMECs in the HG group significantly increased (P<0.05) in both mono-and co-culture models. Migration and lumen formation abilities of RRMECs in the co-culture with HG were lower than that in the monoculture group (P<0.05). The viability of RGCs cells with HG significantly decreased in both mono-and coculture models (Pmono<0.001, Pco<0.001), the apoptosis index of RGCs in the co-culture with HG was higher than that in the monoculture (P=0.010). The protein and gene expression of OCLN, and ZO-1 in RRMECs significantly decreased with HG culture medium in both culture models (P<0.05). In the HG group, the protein and gene expression level of the ZO-1 and OCLN of RRMECs significantly decreased in the co-culture model than that in the monoculture model (P<0.05).Compared with mono cell culture, the established co-culture in vitro system for diabetic neurovascular dysfunction can better stimulate the micro-environment of the retinal neurovascular unit.